Turnover in Financial Service Startups in Indonesia: The Mediating Effects of Civility, Job Satisfaction, and Affective Commitment - Al Fitra Netera Anfal; Gilang Pratama Hafidz (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Startup companies enter the market with innovative products or services, operating in dynamic environments with limited resources. Dynamic business environments require organizations to pay attention to human resources, as employees are valuable assets. Startups experience high turnover rates, which disrupt business processes. This study aims to understand the factors and the importance of turnover in the top 10 financial service startups in Indonesia, with a sample of permanent staff with at least 1 year experience. Data collection was obtained through online questionnaires. Structural Equation Model (SEM) was used to test the research model with a sample size of 138 respondents. The results indicate that managerial support for employees and employees' perception of fairness towards the organization impact civility, known to increase employee job satisfaction, which in turn mediates civility with turnover intention, ultimately increasing affective commitment to reduce turnover intention. The study is limited to focusing on the top 10 financial service startups in Indonesia and does not explore the roles of age, gender, and job type differences, thus the results do not encompass the entire startup environment and its employees' personal factors. Future studies are expected to explore these aspects to provide deeper insights in subsequent research.